MATHEMATICAL MODELING OF VARICELLA TRANSMISSION USING SVEITR MODEL - Sadiyana Yaqutna Naqiya; Vina Lusiana; Achmad Abdurrazzaq (PATTIMURA UNIVERSITY, 2026)
Varicella is a highly contagious disease with strong potential to persist endemically if not adequately controlled. This study develops an SVEITR (Susceptible–Vaccinated–Exposed–Infected–Treated–Recovered) model by extending the SVEIR and SEITR frameworks with a treatment compartment to represent individuals receiving medical care. A mathematical modeling approach was applied through differential equation formulation, equilibrium stability analysis, and computation of the basic reproduction number using the Next Generation Matrix method. The results show that , confirming a high transmission potential. Numerical simulations indicate that vaccination and treatment reduce disease spread, yet waning immunity sustains a pool of susceptible individuals. These findings highlight the importance of continuous control strategies. The inclusion of a treatment compartment represents a methodological advancement, providing a more comprehensive framework for evaluating the effects of interventions on varicella transmission.